Potensi Desa Leran Kulon sebagai Desa Wisata di Kecamatan Palang, Kabupaten Tuban - Kusumaningayu, Intan; Rolalisasi, Andarita; Iffiyah, Khoudiy; Hutama, Shinta Fiqi (Universitas Aisyiyah Yogyakarta, 2020)
This paper is about the architecture and tourism that is the tourism potential of Leran Kulon, Tuban District, East Java. This village potencies consists of the natural resources, the human resources, an infrastructure resources and a supporting institution. The method used qualitative research method that data collected through interview, observation, and literature review. The result showed that Leran Kulon Village potencies are the fabulous natural landscape and the local wisdom that will develop as a tourist attraction.